A Systematic Literature Review on the Determinants of Community Welfare - Muhsin Noh Bailusy; Abdul Hadi Sirat; Hartaty Hadady; Ida Hidayanti (International Journal of Applied Business and International Management, 2026)
Issues of cognitive decline, family income, and caregiving responsibilities are increasingly integrated in the study of societal well-being. This systematic literature review aims to evaluate and synthesize research on the impact of income, a husband's cognitive decline, and family responsibilities on societal well-being. Using PRISMA, a systematic search in the Scopus database for articles published between January 2019 and April 2024 identified six articles that met the inclusion criteria. The synthesis results of these articles show that only the influence of income and welfare was found from a total of 882 articles. The results showed no relationship between the husband's cognitive decline and family responsibilities and community welfare; only the relationship between income and community welfare was found in this study. Apart from that, the results also show that most of the research was carried out in the economic, regional economic, forestry, and agricultural sectors. Furthermore, theories identified in the reviewed studies include income welfare theory, material welfare theory, Keynesian economic theory, Friedmann and Douglass’ theory, and political theory. These findings highlight the dominant role of income in community welfare, while indicating limited empirical attention to husbands’ cognitive decline and family responsibilities, underscoring the need for further research.